Interkinetic nuclear migration in the mouse embryonic ureteric epithelium: Possible implication for congenital anomalies of the kidney and urinary tract. (May 2016) - Motoya, Tomoyuki; Ogawa, Noriko; Nitta, Tetsuya; Rafiq, Ashiq Mahmood; Jahan, Esrat; Furuya, Motohide; Matsumoto, Akihiro; Udagawa, Jun; Otani, Hiroki
Abstract: Interkinetic nuclear migration (INM) is a phenomenon in which progenitor cell nuclei migrate along the apico‐basal axis of the pseudostratified epithelium, which is characterized by the presence of apical primary cilia, in synchrony with the cell cycle in a manner of apical mitosis. INM is suggested to regulate not only stem/progenitor cell proliferation/differentiation but also organ size and shape. INM has been reported in epithelia of both ectoderm and endoderm origin. We examined whether INM exists in the mesoderm‐derived ureteric epithelium. At embryonic day (E) 11.5, E12.5 and E13.5, C57BL/6J mouse dams were injected with 5‐bromo‐2'‐deoxyuridine (BrdU) and embryos were killed 1, 2, 4, 6, 8, 10 and 12 h later. We immunostained transverse sections of the ureter for BrdU, and measured the position of BrdU (+) nuclei in the ureteric epithelia along the apico‐basal axis at each time point. We analyzed the distribution patterns of BrdU (+) nuclei in histograms using the multidimensional scaling. Changes in the nucleus distribution patterns suggested nucleus movement characteristic of INM in the ureteric epithelia, and the mode of INM varied throughout the ureter development. While apical primary cilia are related with INM by providing a centrosome for the apical mitosis, congenital anomalies of the kidney and urinary tract (CAKUT) include syndromes linked to primary ciliary dysfunction affecting epithelial tubular organs such as kidney, ureter, and brain. The present study showed that INM exists in the ureteric epithelium and suggests that INM may be related with the CAKUT etiology via primary ciliary protein function.